On Qualitative Analysis for Time-Dependent Semi-Linear Fractional Differential Systems - Matar, Mohammed M.; Alzabut, Jehad O.; Abbas, Mohamed I.; Awadalla, Muath Muhammed; Mahmudov, Nazim Idrisoglu (Natural Sciences Publishing, 2022)
This paper investigates some qualitative properties of solutions for fractional differential systems. Particularly, we focus on existence, uniqueness, priori bounds, and dependence on parameters for the solution. Reported results are proved via fixed point theorems and Pachpatte inequality. Unlike most of previous results, the existence theorem is proved under non-Lipschitzian condition. This work is supported with an example to validate the obtained results applicability © 2022 NSP Natural Sciences Publishing Cor
Keywords: Dependence on parameters; Existence; Fixed point theorems; Priori bounds; Semi-linear fractional differential system; Uniqueness